The Essence of Rationality Concept in Contracting Islamic Economics Business - Wahyudi, Trubus (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This research aims to know the paradigm of sharia economic business contracting activities carried out by humans as God's caliphs on earth should be carried out in good faith and understand the concept of contractual rationality and the obligation to help each other in carrying out Islamic economic activities which aim, among other things, to worship Allah SWT. Humans are ordered to believe in the Day of Judgment, because all the behavior of human economic activities will be controlled and he is aware that all his actions will be held accountable later by Allah SWT. In the matter of contracting/agreements, Islam provides guidelines as stated in the letter Al Isra'(17) verse 34 which means: